If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + 21(x + -2) = 318 Reorder the terms: 15x + 21(-2 + x) = 318 15x + (-2 * 21 + x * 21) = 318 15x + (-42 + 21x) = 318 Reorder the terms: -42 + 15x + 21x = 318 Combine like terms: 15x + 21x = 36x -42 + 36x = 318 Solving -42 + 36x = 318 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 42 + 36x = 318 + 42 Combine like terms: -42 + 42 = 0 0 + 36x = 318 + 42 36x = 318 + 42 Combine like terms: 318 + 42 = 360 36x = 360 Divide each side by '36'. x = 10 Simplifying x = 10
| 4x^2+7-3=0 | | 19x-(4x-9)=84 | | 19x-3(4x-9)=84 | | 5m+10=9m-2 | | 5(6z+1)-9=146 | | 3(4x-1)=36 | | (-6)(9)= | | (4-9)= | | 4w^2=-12w-5 | | [10-2]= | | 12*-72= | | 14y=-84 | | v+-391=1255 | | v+-391=255 | | 8(4+4(5))= | | v+255=-391 | | 8(4+5(5))= | | -5(2x+1)=1-4(x+9) | | (x-5)(2x^2+3x-1)= | | 3(x+9)=42 | | X^6+5x^3-6=0 | | x(x)+5x+6=0 | | x(x)-5x-6=0 | | (3x^2-4x+10)-(x^2-9x+13)= | | c+150=1860 | | 5x(x)=6+2x | | x-13=-3 | | (2x^2-x+7)+(3x^2+x-9)= | | x(x)-7x-8=0 | | (40x)+(20*1.5x)=1625 | | 2-4y=4-5y | | 7y+3=6y-2 |